A review on the emergence and growth of halal studies - Noreen Noor Abd Aziz; Nurul Aien Abd. Aziz; Nurul Ashykin Abd Aziz; Zurina Omar; Wan Haslin Aziah Wan Hassan (2015)
Malaysia is a multiracial country with Islam being the largest practiced religion. One of the most important concepts in Islam is the concept of halal. Halal industry plays an important role in the whole world, especially for Muslim society. The demand for halal product either for food or non-food product has been increasingly from day to day. The study aims to finding out the applicable of Theory of Planned Behaviour (TPB) in halal studies. Thus, this paper aims to know whether any systematic literature review on halal studies with the use of Theory Planned Behaviour has been done especially on various products such as cosmetic, food and etc. The literature review will be based on 17 articles and journals relating to halal studies. The journals and articles have been selected from various databases between year 2007 – 2014. The main objective is to identify the trends (year) on halal studies with the use of Theory of Planned Behaviour. The second objective is to identify the themes use in halal studies. In conclusion, it is hope that this paper will offer directions for future research in halal study with the use of Theory of Planned behaviour (TPB) model.